2019
DOI: 10.1177/1066896919883679
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Appendiceal Mucinous Neoplasms: A Single Institution Experience of 64 Cases With Clinical Follow-up and Correlation With the Current (Eighth Edition) AJCC Staging

Abstract: Background. In this single-institution study, we applied the current (eighth edition) American Joint Committee on Cancer pathologic staging criteria to 64 low-grade mucinous neoplasms of the appendix (LAMNs), examined their histopathologic features, and studied the patients’ clinical outcomes. Design. Sixty-four LAMNs, with a median follow-up of 52 months, were reviewed. Results. The distribution of pathologic stages was pTis (n = 39), pT3 (n = 1), pT4a (n = 5), pT4aM1a (n = 8), and pT4aM1b (n = 11). Recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This conclusion was compatible with other studies. 5,10,18 PLR-H may indicate higher rate of PMP (p = 0.01); however, unfortunately, both NLR-H and PLR-H could not be used as predictors of cellular ascites. Therefore, cautious handling of mucinous appendiceal tumors during surgery is crucial to avoiding perforation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This conclusion was compatible with other studies. 5,10,18 PLR-H may indicate higher rate of PMP (p = 0.01); however, unfortunately, both NLR-H and PLR-H could not be used as predictors of cellular ascites. Therefore, cautious handling of mucinous appendiceal tumors during surgery is crucial to avoiding perforation.…”
Section: Discussionmentioning
confidence: 98%
“…These patient characteristics and treatment outcomes were compatible to other larger cohort studies. 18,19 However, due to indolence, and low malignancy of LAMN, complete cytoreduction brought lower recurrent rate than other gastrointestinal tract cancers, even in M stage diseases. 5,20 Therefore, we used RFS instead of disease-free survival or progression-free survival in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the work of Misdraji et al [14] in 2003, as outlined in the World Health Organization (WHO) Classification of Digestive System Tumors (2019), malignant mucinous neoplasms of the appendix can be divided into two categories as follows: LGMN (characterized by a low-grade neoplastic mucinous epithelium with extracellular mucin and thrusting tumor margins) and mucinous adenocarcinoma (characterized by infiltrative invasion).…”
Section: Discussionmentioning
confidence: 99%
“…Two prior studies found no recurrence of disease following resection of nonmetastatic LAMN with a median follow-up of 4-5 years. 11,12 However, these studies were limited by low power and lack of stratification based on the extent of resection, and therefore, the true incidence of recurrence after resection of localized LAMNs is unclear. Furthermore, because these studies included few patients with T3-T4 lesions or did not evaluate T-category, the conclusions that can be drawn regarding higher T-category localized LAMNs are limited.…”
Section: Introductionmentioning
confidence: 99%